The Big Pine Bark Of The Fargoga Valley (Texas Journal of Agriculture and Biological Sciences, 2023)
Large pine bark beetle - Scolytus scolytus (Fabricius, 1775) is a polyphagous insect, it is widespread in Eurasia, as well as in all regions of Uzbekistan